Development and In vitro and In vivo Evaluations of a Microemulsion Formulation for the Oral Delivery of Oxaprozin - Yin, Fangming; Meng, Shu; Zhao, Xin; Wang, Huining; Ning, Yingkai; Li, Yangdulin; Chen, Zaixing (Current Drug Delivery, 2022)
Background: Oxaprozin is labeled as a Class II drug in the biopharmaceutical classification system, and its poor solubility in the entire gastrointestinal tract may be the main reason for its insufficient oral absorption capacity. Objective: The purpose of this study was to develop an oxaprozin formulation to enhance its oral absorption. Methods: Oxaprozin-loaded microemulsions were prepared using the titration method and pseudoternary phase diagram. Characterization experiments were performed on microemulsion preparations, including pH, particle size, shape, zeta potential, and stability (thermodynamic, dilution, and differential scanning calorimetry). Then, the in vitro release of the microemulsion and in vivo pharmacokinetics in rats were evaluated. Results: Several microemulsion formulations were prepared. The optimal formulation was 15% oleoyl macrogolglycerides, 35% Tween 20/isopropanol (Km=2), and 50% distilled water. Its particle size met the requirements, and it had a spherical shape with a negatively charged surface. This microemulsion-loaded drug was applied to in vitro release and in vivo pharmacokinetic experiments at 7.47 mg/mL. In vitro release of the oxaprozin-loaded microemulsion best fit the firstorder model, while the microemulsion preparation had a certain sustained-release effect. In vivo pharmacokinetic experiments indicated that the microemulsion formulation significantly delayed the peak time of the blood concentration and simultaneously prolonged the half-life of drug elimination. Conclusion: The obtained data revealed satisfactory results for this novel microemulsion of oxaprozin, which is very meaningful for clinical trials.
Keywords: transmission electron microscopy